ASSA14-03-29 Angiographic features of patients with atherosclerosis in the segments proximal to the myocardial bridge. (1st December 2014) - Jian, Z; Ya-Ling, H; Quanmin, J; Xiaozeng, W; Ying-Yan, M; Geng, W; Bin, W
Abstract : Backgroud: By studing the clinical and imaging features of myocardial bridge and severe atherosclerosis lesions in the segments proximal to the myocardial bridge, compared with that of pure myocardial bridge retrospectively, to analyse the clinical and imaging characteristics of these patients. Methods: The study population consisted of 2 groups (192 patients). The CHD Group included 92 patients with severe atherosclerosis lesion of luminal narrowing of ≥70% in the segments proximal to the myocardial bridge. The bridge group included 100 patients with symptomatic myocardial bridge lesion of systolic luminal narrow. All lesions were successfully treated with stent by standard interventional techniques. Quantitative coronary angiography was performed before and immediately after stent deployment. Results: The mean age and systolic pressue in the CHD patients were more than that in the pure bridge group (58 ± 11 vs 42 ± 10y and 157.8 ± 9.8 vs 146.1 ± 10.2 mmHg, respectively), p < 0.05. No significant difference was found between two groups such as gender, DM, smoking, hyperlipidemia, old myocardial infarction percentage. There was a significant difference in the extent of diameter stenosis during systolic stage between CHD and bridge groups (95 ± 5% vs 90 ± 7%). But the average length from the proximal end of myocardial bridge to the ostium of LAD and the average length of myocardial bridge had not difference between two groups. Conclusions: The patients with severe atherosclerosis lesion in the segments proximal to the myocardial bridge has more risk factors of CHD, the extent of diameter stenosis during systolic stage has some promotive effect to CHD.